(untitled) (Archaeologia Adriatica, 2017)
The article deals with two fragments of a ceramic object found in the excavations of the Neolithic site of Smilčić. Owing to their physical joining it was possible to suggest a reconstruction which depicts front of an object which corresponds fully to concept of a Neolithic house with stylized depiction of horns placed above the entrance. Minimally preserved lateral side on the right fragment suggest very convincingly a conclusion that this was not depiction of the front only but model of entire object which resembles a Neolithic house. However the author believes that this was not depiction of a Neolithic house but of a Neolithic sanctuary functioning as altar.